Factors affecting CO2 emissions in Indonesia 1985-2021 - Rani Salsabila Nadiani (Efficient: Indonesian Journal of Development Economics, 2023)
This study aims to determine and analyze the effect of urban population, per capita income, per capita income2, oil consumption and natural gas consumption on CO2 emissions in Indonesia in 1985-2021.This study uses the Autoregressive Distributed Lag (ARDL) method. The results show that the variables of urban population, per capita income, per capita income2, oil consumption, natural gas consumption have a positive effect on CO2 emissions in the short term, while in the long term the variables of urban population, per capita income and natural gas consumption have no effect on CO2 emissions in the long term. The Environmental Kuznets Curve Hypothesis (EKC) is proven in Indonesia.